2009
DOI: 10.1111/j.1745-9125.2009.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Land Use and Violent Crime*

Abstract: 1 LAND USE AND VIOLENT CRIMEAlthough research has shown specific land uses to be related to crime, systematic investigation of land uses and violent crime has been less common. This study systematically examines links between land uses and violent crime and whether such links are conditioned by socioeconomic disadvantage. We employ geocoded UCR data from the Indianapolis police department and information on 30 categories of land use, and demographic information from the 2000 census. We use land use variables t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(193 citation statements)
references
References 54 publications
8
180
1
4
Order By: Relevance
“…In other words, if a significantly greater amount of crime takes place on more permeable street segments, is this simply because such segments host more (crime-attracting or -generating) land uses? Research has shown that particular land uses, such as entertainment, commercial and transport-related facilities, are related both to the spatial distribution of crime (e.g., Browning et al 2010;Kinney et al 2008;McCord and Ratcliffe 2009;Stucky and Ottensmann 2009;Weisburd et al 2012Weisburd et al , 2014 and the configuration of the street network (Hillier 1996(Hillier , 2007Peponis 2004). However, the joint influence of these two factorsland use and street network configuration-on crime has not previously been examined, raising the possibility that the conclusions of previous research might be spurious.…”
Section: Space Syntaxmentioning
confidence: 69%
“…In other words, if a significantly greater amount of crime takes place on more permeable street segments, is this simply because such segments host more (crime-attracting or -generating) land uses? Research has shown that particular land uses, such as entertainment, commercial and transport-related facilities, are related both to the spatial distribution of crime (e.g., Browning et al 2010;Kinney et al 2008;McCord and Ratcliffe 2009;Stucky and Ottensmann 2009;Weisburd et al 2012Weisburd et al , 2014 and the configuration of the street network (Hillier 1996(Hillier , 2007Peponis 2004). However, the joint influence of these two factorsland use and street network configuration-on crime has not previously been examined, raising the possibility that the conclusions of previous research might be spurious.…”
Section: Space Syntaxmentioning
confidence: 69%
“…Thus, we need to know not only where the residential population lives, but we must also know their likely destinations during the day to obtain estimates of the number of people on a block during particular hours of the day, or what is referred to as "ambient population" (Andresen 2011;Malleson and Andresen 2016). Nonetheless, much of the research studying crime in small geographic units focuses only on presence of criminal opportunities at locations, which does not take into account the relative presence of offenders at a location, which is an equally important component of the theory (Groff and Lockwood 2014;Stucky and Ottensmann 2009). For example, although a bar provides criminal opportunities, the amount of crime experienced there will likely differ if there are relatively few potential offenders in the surrounding area compared to a bar with a relatively high number of offenders in the surrounding area (Hipp 2016).…”
Section: Theories Of the Spatial Patterning Of Crimementioning
confidence: 99%
“…Residential maintenance and improvement may be stifled if their core locations are under pressure for redevelopment for higher density residential or commercial projects, or transition to adaptive non-residential uses [31] [50]. Excluding redevelopments for higher density projects, they still tend to have higher density housing and more mixed land uses with less spacing between them than in newer suburbs, rural areas or small towns [62].…”
Section: Residents and Properties In Older-urban Residential Neighboumentioning
confidence: 99%